[Supplemental material] Comparative study of benznidazole encapsulation in boron nitride and carbon nanotubes: A quantum chemistry study - Santos, Jeziel Rodrigues; de Oliveira, Osmair Vital; Viegas, Rafael Giordano; dos Santos, José Divino; Longo, Elson (Eclética Química, 2022)
Quantum chemistry methods were used to study boron nitride and carbon nanotubes as possible carriers of antichagasic benznidazole to improve their water solubility and bioavailability. Structurally, no significant changes were observed in both nanotubes throughout the encapsulation process. For the BNZ@BNNT complex, it was possible to notice short interactions, at 0.215 nm, between the hydrogen atoms of the BNZ and the nitrogen atoms of the BNNT. The binding energy reveals that both nanotubes are capable of encapsulating BNZ in an aqueous medium, with values of –71.79 and –62.68 kcal/mol for the BNZ@BNNT and BNZ@CNT complexes. The enthalpy of solvation indicates that the complexes are soluble in water with values of –32.35 and –28.76 kcal mol–1 for the BNZ@BNNT and BNZ@CNT complexes. Regarding chemical stability, Eg and η show that BNZ@BNNT has greater stability (Eg/η of 3.35/1.68 eV) than BNZ@CNT (0.16/0.08 eV). Overall, our results demonstrate that BNNT is a better candidate to be used as a carrier of BNZ than CNT due to its greater structural and chemical stability.